Performance comparisons of new excitation coil design aspects in Magnetic Induction Tomography (MIT) applications - Zulkarnay, Zakaria; Muhamad Hafiz, Hussin; Ruzairi, Abdul Rahim; Nur Farahiyah, Mohammad; Azian Azamimi, Abdullah; Sazali, Yaacob, Prof. Dr.; Syed Mustafa Kamal, Syed Aman (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/